2022
DOI: 10.3390/jcm11092628
|View full text |Cite
|
Sign up to set email alerts
|

Peri-Implant Distal Radius Fracture: Proposal of a New Classification

Abstract: A peri-implant fracture near the volar plate of the distal radius represents a rarity and can be associated with a mechanical failure of the devices. A literature review was conducted including all fractures that occurred around a volar wrist plate, which could be associated with an ulna fracture. All articles published until December 2021 were considered according to the guidelines presented in the PRISMA Statement. The search was conducted with the PubMed electronic database, Cochrane Database of Systematic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…The surgical methods employed for wrist implants can determine post-operative outcomes. In our study the treatment did not completely follow the therapeutic algorithm recommended by Stramazzo in his article according to the new classification [ 22 ]. We replace the plate with a DCP plate, not with a longer anatomical plate because it was not available at the time of surgery.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…The surgical methods employed for wrist implants can determine post-operative outcomes. In our study the treatment did not completely follow the therapeutic algorithm recommended by Stramazzo in his article according to the new classification [ 22 ]. We replace the plate with a DCP plate, not with a longer anatomical plate because it was not available at the time of surgery.…”
Section: Discussionmentioning
confidence: 94%
“…Such fractures commonly present as stress fractures that occur in close proximity to the distal end of the implant. Based on the fracture level and the specific type of plate failure, we applied the classification proposed by D'Arienzo for peri-implant wrist fractures, categorizing it as type C1U (radius fractures occur proximally, within 3.5cm from the plate and in association with a fracture of the ulna) [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…Other authors considered different bones than the femur: Stramazzo et al [26] reviewed all cases of peri-implant radius fracture reported in the literature and described a new classification for this type of fracture.…”
Section: Discussionmentioning
confidence: 99%
“…Purpose of fracture treatment is to achieve the union of the bone fragments [ 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 ]. Moreover, it is to restore the function of the musculoskeletal system and prevent future complications associated with the failure of restoration of the normal anatomy [ 10 , 11 , 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%